The perfect stranger - Miranda, Megan (New York : Simon & Schuster, 2017)
"In the masterful follow-up to the runaway hit All the Missing Girls--a "fiendishly plotted thriller" (Publishers Weekly)--a journalist sets out to find a missing friend, a friend who may never have existed at all. Confronted by a restraining order and the threat of a lawsuit, failed journalist Leah Stevens needs to get out of Boston when she runs into an old friend, Emmy Grey, who has just left a troubled relationship. Emmy proposes they move to rural Pennsylvania, where Leah can get a teaching position and both women can start again. But their new start is threatened when a woman with an eerie resemblance to Leah is assaulted by the lake, and Emmy disappears days later. Determined to find Emmy, Leah cooperates with Kyle Donovan, a handsome young police officer on the case. As they investigate her friend's life for clues, Leah begins to wonder: did she ever really know Emmy at all? With no friends, family, or a digital footprint, the police begin to suspect that there is no Emmy Grey. Soon Leah's credibility is at stake, and she is forced to revisit her past: the article that ruined her career. To save herself, Leah must uncover the truth about Emmy Grey--and along the way, confront her old demons, find out who she can really trust, and clear her own name. Everyone in this rural Pennsylvanian town has something to hide--including Leah herself. How do you uncover the truth when you are busy hiding your own?"--
Keywords: FICTION / Contemporary Women; FICTION / Suspense; FICTION / Coming of Age; Suspense fiction; Mystery fiction